Una especie nueva de rana arbórea del género Hyloscirtus (Amphibia: Anura: Hylidae) de la Cordillera del Cóndor - Almendáriz, Ana; Brito, Jorge; Batallas, Diego; Ron, Santiago (Papéis Avulsos de Zoologia, 2014)
Ecuadorian frogs of genus Hyloscirtus comprises 16 described species, of which eleven belong to the H. larinopygion group. They are restricted to the flanks of the Andes, both east and west. An assessment of the herpetofauna in the southern part of Cordillera del Condor (montane forests on sandstone plateaus) province of Zamora Chinchipe, Ecuador, led to the discovery of a new species for the group, which we describe herein as Hyloscirtus condor sp. nov. We herein analyze the tadpoles and advertisement calls, as well as estimate the phylogenetic relationships of the new and related species, based on new sequences of mitochondrial genes 12S, tRNA Val y 16S, until a total of 2508 bp. The results show that the group H. larinopygion comprises two clades: one occurring in the northern and central Andes, and the second in the south. The new species belongs to the southern clade, is sister to H. tapichalaca, and a seemingly undescribed species from Provincia Morona Santiago. The new species differs from all its congeners in color pattern, which consists of dark yellow dots on a tan background. It is the largest species of the H. larinopygion group and shares with H. tapichalaca the presence of a large prepollical curved spine and hypertrophied forearms. The new species inhabits a remote and well-preserved area of Cordillera del Condor. The discovery of new species and others at the site denotes the biological importance of this area and encourages the development of conservation plans.